The Prevalence and Incidence of Frontotemporal Dementia: a Systematic Review. (April 2016) - Hogan, David B.; Jetté, Nathalie; Fiest, Kirsten M.; Roberts, Jodie I.; Pearson, Dawn; Smith, Eric E.; Roach, Pamela; Kirk, Andrew; Pringsheim, Tamara; Maxwell, Colleen J.
Abstract: Background: Population-based prevalence and incidence studies are essential for understanding the burden of frontotemporal dementia (FTD). Methods: The MEDLINE and EMBASE databases were searched to identify population-based publications from 1985 to 2012, addressing the incidence and/or prevalence of FTD. References of included articles and prior systematic reviews were searched for additional studies. Two reviewers screened all abstracts and full-text reviews, abstracted data and performed quality assessments. Results: Twenty-six studies were included. Methodological limitations led to wide ranges in the estimates for prevalence (point prevalence 0.01-4.6 per 1000 persons; period prevalence 0.16-31.04 per 1000 persons) and incidence (0.0-0.3 per 1000 person-years). FTD accounted for an average of 2.7% (range 0-9.1%) of all dementia cases among prevalence studies that included subjects 65 and older compared to 10.2% (range 2.8-15.7%) in studies restricted to those aged less than 65. The cumulative numbers of male (373 [52.5%]) and female (338 [47.5%]) cases from studies reporting this information were nearly equal ( p =0.18). The behavioural variant FTD (bvFTD) was almost four times as common as the primary progressive aphasias. Conclusions: Population-based estimates for the epidemiology of FTD varied widely in the included studies. Refinements in the diagnostic process, possibly by the use of validated biomarkers or limiting case ascertainment to specialty services, are needed to obtain more precise estimates of the prevalence and incidence of FTD. RÉSUMÉ: Prévalence et incidence de la démence fronto-temporale : une revue systématique du sujet. Contexte : Les études de population sur la prévalence et l'incidence sont essentielles à la compréhension du fardeau associé à la démence fronto-temporale (DFT). Méthodologie : Nous avons cherché dans les bases de données MEDLINE et EMBASE les articles publiés entre 2000 et 2012 portant sur l'incidence et/ou la prévalence de la DFT dans la population. Nous avons également examiné les références des articles inclus dans notre étude ainsi que celles des revues systématiques antérieures. Deux évaluateurs ont examiné tous les résumés et le texte intégral des publications et l'extraction des données, et ils en ont évalué la qualité. Résultats : Vingt-six études ont été retenues. Des limites méthodologiques expliquent les écarts dans les estimations de prévalence (prévalence ponctuelle de 0, 01 à 4, 6 par 1 000 ; prévalence d'une période donnée de 0, 16 à 31, 04 par 1 000) et incidence (0, 0 à 0, 3 par 1 000 personnes-années). La DFT constituait en moyenne 2, 7% (écart de 0 à 9, 1%) de tous les cas de démence dans les études de prévalence qui incluaient des sujets de 65 ans et plus par rapport à 10, 2% (2, 8 à 15, 7%) dans les études portant sur des sujets âgés de moins de 65 ans. Les nombres cumulatifs d'hommes (373 [52, 5%]) et de femmes (338 [47, 5%]) tirés des études dans lesquelles cette information était mentionnée étaient pratiquement égaux (p=0, 18). La variante comportementale DFT était presque quatre fois plus fréquente que les aphasies progressives primaires. Conclusions : Les estimations basées sur la population en ce qui concerne l'épidémiologie de la DFT étaient très variables dans les études que nous avons retenues. Il faudra raffiner le processus diagnostique, possiblement par l'utilisation de biomarqueurs validés ou limitant la constatation des cas à ceux confirmés par des services spécialisés, pour obtenir des estimations plus précises de la prévalence et de l'incidence de la DFT.